A Study of the Intellectual and Cultural Nature of the Al Ziyar Government - Hossein Arabnejad Zarandy, Mahdi farhoudfar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Al Ziyar was one of the first Iranian Shiite dynasties of Dailami who were able to rule different areas from north to central Iran for nearly two centuries. This dynasty was established in the early fourth century AH with the special military and political tactics of Mardavij Ziyari. Al Ziyar after the period of glory and early glory, whose rule in some cases extended to the south and west of Iran; They suffered from weakness and early decline in power, so that sometimes the scope of their rule did not exceed the areas around Gorgan. After a while, they became completely puppets of the Seljuks. Due to the long wars with Al Buwayh and on the other hand due to excessive flexibility, intellectual, cultural and political tolerance with the Sunni states of Samani, Ghaznavid and Seljuk religions; Ziyaris could never take an important step in promoting the ideas of Shiism. Even in the matter of cultural and civilizational achievements for Shiism, their function is not considered much.